The role of war cry and its rhetorical function in Shahname - Hamid Rabiei; Ali Mohammasd Shahsani (مطالعات زبانی و بلاغی)
The essence of Shahname is epical, and epic is based on heroic acts and speech, both of which often take place in relation with battle scenes; as the adversaries enter the battlefield, they must open the conversation before taking any action. So, the first step is verbal communication. One of these conversational styles is war cry and boasting which is conveyed between adversaries orally, written or by means of sending a message for different goals. Theses war cries can be studied from different point of views:Revealing the champion’s sources of relianceArousing the hero to fight and protesting against procrastinationProhibiting war and enticing into procrastinationSuitable approaches to learn about the strength of powerReflecting on moralities and using decent languageThe tone and rhythm of speechThe manner of making war cryStrengthening the sense of national pride patriotism.The manner of using rhetorical techniquesBy pointing to the more significant evidences, this essay briefly examines and analyses the aforementioned statements with an emphasis on manners and insights of Shahnameh characters.